Association of the selected dimensions of eudaimonic well-being with healthy survival to 85 years of age in older women. (December 2014) - Zaslavsky, Oleg; Rillamas-Sun, Eileen; Woods, Nancy Fugate; Cochrane, Barbara B.; Stefanick, Marcia L.; Tindle, Hilary; Tinker, Lesley F.; LaCroix, Andrea Z.; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: Aspects of eudaimonic well-being, such as personal growth (PG) and purpose in life (PL), have been highlighted as important to older adults' health. We investigated the relationship of PG and PL with patterns of survival to the age of 85 years and older. Methods: The sample included 8, 880 women from the Women's Health Initiative cohort who reached 85 years of age by December 1, 2013, and for whom data on the PG and PL constructs were available. Women were classified into mutually exclusive outcomes: Healthy, Prevalent, Incident, Disabled, and Deceased. PG and PL were each assessed using a modified seven-item measure derived from the Psychological Well-Being scale. Results: Women were most commonly classified as Healthy (38.2%, n = 3, 395), followed by Incident (24.4%, n = 2, 163), Disabled (19.0%, n = 1, 685), Prevalent (14.3%, 1, 273), and Deceased (4.1%, n = 364). Women with low PL and PG levels were more likely to have prevalent mobility disability and disease or incident death before the age of 85 years. Specifically, those who reported low levels of PG and PL had a 2.1- and 3.6-fold higher risk, respectively, of death. Conclusions: These findings indicate that even among the oldest old, experience of purposeful life engagement and continuing PG may contribute to better health outcomes.